Faktor-Faktor yang Memengaruhi Niat Berwirausaha Mahasiswa Muslim dalam Perspektif Islam: Studi Kasus di Universitas Padjadjaran - Nisrina Nur Aini Marwah; Vita Sarasi (Journal of Islamic Economics and Finance, 2025)
Young generation dominated the unemployment rate in Indonesia, highlighting the need to increase the number of entrepreneurs to create new job opportunities. However, the number of entrepreneurs, particularly Muslim entrepreneurs, remained relatively low. To encourage individuals to do entrepreneurship in the future, a strong entrepreneurial intention is required. Thus, this study aims to analyze the factors that influence the entrepreneurial intention of Muslim students from internal and external aspects and from an Islamic perspective. These factors included self-efficacy, family support, peer support, and institutional support with knowledge of entrepreneurial skills, risk-taking ability, and innovative behavior as mediators. This research was conducted on 215 Muslim students at Padjadjaran University using a questionnaire and analyzed using SmartPLS. The results showed that self-efficacy, family support, peer support, and institutional support have a positive and significant effect on entrepreneurial intention through mediating variables. Additionally, innovative behavior has a positive and significant effect as a mediator in the research model. These findings provide insights for academics and practitioners to support entrepreneurship development, especially among Muslim students.